RANCANG BANGUN SISTEM MONITORING SUHU COLD STORAGE BERBASIS IOT MENGGUNAKAN WEMOS D1 R2 DI PT. AEROFOOD ACS DENPASAR - Diky Wahyu Kusuma Budi; Rukmi Sari Hartati; I Gede Dyana Arjana (Program Studi Teknik Elektro UNUD, 2022)
Monitoring temperature and humidity in cold storage is very important to prevent damage to food raw materials. Checking the temperature in the cold storage is carried out every 4 hours with the results manually written on the log sheet by the working staff and also sometimes there are staff who do not close the cold storage door tightly so that it causes an increase in temperature. Therefore an IoT-based cold storage temperature monitoring system is created using Wemos D1 R2 in real time which is very necessary. The design of this prototype uses hardware, namely the WeMos D1 R2 microcontroller because it is based on ESP8266 which can be connected to WiFi, DHT22 temperature sensor, and HC-SR501 PIR sensor. The software used is blynk and google spreadsheet. The results of this prototype design are being able to read the cold storage temperature and humidity properly which can be seen in the blynk application on a smartphone by displaying the temperature and humidity values. This prototype also has a feature that sends notifications to smartphones when the temperature is read more than 5°C and has temperature data stored on Google spreadsheets. The conclusion of this study has succeeded in designing and making a prototype of an IoT-based cold storage temperature monitoring system. The testing of the prototype can work well. The results of applying the prototype to cold storage Room 21 obtained an average temperature of 2.9°C and an average humidity of 86%.